Epidemiological Factors of Cleft Lip and Palate Children: A Cross-Sectional Study in Northern Region of Bangladesh - Howlader, Latifa; Hossain, Abul; Uddin, Gias; Yeasmin, Tanzima (Journal of Bio-Science, 2024)
The life-threatening or potentially-disabling nature of congenital anomalies, which are defined as abnormalities of anatomy, function, or metabolism apparent at birth, makes them a serious public health problem. To evaluate the oral health status and measure the prevalence of nutritional deficiency of cleft lip and palate children. All patients with cleft lip and/or palate treated at Thengamara Mohila Sabuj Sangha (TMSS) Medical College, Bogura, and Islami Bank Medical College, Rajshahi, Bangladesh, participated in this cross-sectional study. A purposive sample of sixty individuals from the general population was used in the investigation. It was revealed that majority (35.0%) of the respondents were in the age group of six months to one year with unilateral cleft lip and palate (63.3%). The majority of the babies (33.3%), 60.0%, were born weighing less than 2.5 kg, and 63.3% were born weighing 4-10 kg. About 80.0% were from urban area 41.67% lived in tin shade house, 65.0% used wood stoves for cooking their food, 35.0% had electric device like TV and refrigerator. It was found that, 55.0% had feeding problems associated with their cleft lip and palate. Regarding monthly family income, it was found that, 33.3% had <10,000 taka as monthly family income. On the subject of fathers’ occupation, 36.6% were farmers, 58.3% of the mothers were housewife. Concerning education of father, 38.33% did not have any education, 53.3% of the mothers did not have any education. About 63.33% of the respondents’ fathers were in the age group of 20-35 years, 70.0% of the mothers were in the age group of 20-35 years. This study would help to assess the cleft lip and palate among the children and make their parents aware. J. Bio-Sci. 31(2): 35-43, 2023